Metallo-β-Lactamases and Aptamer-Based Inhibition - Sung-Kun Kim; Taylor O. Foster; Mieke J. Lahousse; Sara R. Schlesinger (MDPI AG, 2011)
An evolution of antibiotic-resistant bacteria has resulted in the need for new antibiotics. β-Lactam based drugs are the most predominantly prescribed antibiotics to combat bacterial infections; however, production of β-lactamases, which catalyze the hydrolysis of the β-lactam bond of this class of antibiotics, by pathogenic bacteria such as Bacillus cereus, are rendering them useless. Some inhibitors of β-lactamases have been found, but there are no inhibitors against a class of β-lactamases known as metallo-β-lactamases, and it has been reported that the number of bacteria that produce metallo-β-lactamases is on the rise. Finding inhibitors of metallo-β-lactamases is thus an urgent necessity. One way to approach the problem is by employing the combinatorial method SELEX. The SELEX method is significant in discovering and producing new classes of inhibitors, as well as providing insight into the development of these inhibitors and paves the way for future aptamer applications that further novel drug discovery.